2003
DOI: 10.1053/jhep.2003.50026
|View full text |Cite
|
Sign up to set email alerts
|

Octreotide treatment of hepatocellular carcinoma

Abstract: We read with interest the report by Yuen et al. on treatment of hepatocellular carcinoma (HCC) with octreotide published in HEPA-TOLOGY. 1 Their conclusions are different from our study, 2 recently confirmed with long-acting somatostatin analogues. 3 We found a clear survival benefit for treated patients. In the study of Yuen et al., the control group had a poor survival of 1.9 months. This is surprising, since 82% of their patients were Okuda stage I and II, which, according to the original Okuda study should… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
5
0
2

Year Published

2004
2004
2018
2018

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 9 publications
1
5
0
2
Order By: Relevance
“…So, our study will certainly help newly discovered subjects with moderate or higher expected survival. This was confirmed by Kouroumalis et al [44].…”
Section: Percentage Changesupporting
confidence: 67%
“…So, our study will certainly help newly discovered subjects with moderate or higher expected survival. This was confirmed by Kouroumalis et al [44].…”
Section: Percentage Changesupporting
confidence: 67%
“…The somatostatin analogue octreotide has been used for the treatment of HCC with variable results [18][19][20][21], probably due to differences between studies in the selection of patients and disease etiology [31]. It appears that the presence of ssts may be important for tumor response to octreotide treatment [20].…”
Section: Discussionmentioning
confidence: 99%
“…Selection of patients is critical in any study of HCC treatment [18,130,132] . It seems that SST is suitable for patients with viral cirrhosis ideally after identification of the expression on the tumor of SSTR2 and 5, either with scintigraphy or even better by immunofluorescence after a liver biopsy.…”
Section: Resultsmentioning
confidence: 99%
“…The first negative randomized controlled study was reported by Yuen et al [129] . It has been heavily criticized by us and many others, because the selected patients had a very short survival of 1.9 months in the control group (n = 35) vs. 2 months in the octreotide group (n = 35) indicating that most patients belonged to BCLC stage D. In fact 21/35 patients received either none or just one long-acting octreotide injection [130] .…”
Section: Unfavorable Datamentioning
confidence: 99%